Static lung compliance and body pressures in Tupinambis merianae with and without post-hepatic septum - Klein, Wilfried; Abe, Augusto Shinya [UNESP]; Perry, Steven F. (Elsevier, 2003)
The surgical removal of the post-hepatic septum (PHS) in the tegu lizard, Tupinambis merianae, significantly reduces resting lung volume (VLr) and maximal lung volume (VLm) when compared with tegus with intact PHS. Standardised for body mass (MB), static lung compliance was significantly less in tegus without PHS. Pleural and abdominal pressures followed, like ventilation, a biphasic pattern. In general, pressures increased during expiration and decreased during inspiration. However, during expiration pressure changes showed a marked intra- and interindividual variation. The removal of the PHS resulted in a lower cranio-caudal intracoelomic pressure differential, but had no effect on the general pattern of pressure changes accompanying ventilation. These results show that a perforated PHS that lacks striated muscle has significant influence on static breathing mechanics in Tupinambis and by analogy provides valuable insight into similar processes that led to the evolution of the mammalian diaphragm. © 2003 Elsevier Science B.V. All rights reserved.
Keywords: Compliance; Mechanics of breathing; Post-hepatic septum; Reptile; Reptiles; Tegu lizard (Tupinambis merianae); Ventilation; abdominal pressure; animal experiment; body mass; breathing mechanics; controlled study; developmental stage; forced expiratory volume; hysteresis; lizard; lung compliance; lung volume; muscle injury; newborn; nonhuman; priority journal; smooth muscle; thorax pressure; Abdominal Cavity; Animals; Liver; Lizards; Lung; Lung Compliance; Muscle, Smooth; Pleural Cavity; Pressure; Pulmonary Ventilation